The contribution of Ghanaian patients to the reporting of adverse drug reactions: a quantitative and qualitative study - Tom G. Jacobs; H. Hilda Ampadu; Jarno Hoekman; Alexander N. O. Dodoo; Aukje K. Mantel-Teeuwisse (BMC, 2018)
Abstract Background Under-reporting of adverse drug reactions (ADRs) is a major challenge for pharmacovigilance in Africa. This study sets out to assess the level of awareness of Ghanaian patients about ADRs and ADR-reporting and explores how different patients in Ghana recognize an ADR and the steps they take when they experience an ADR. Methods This was a two-part study consisting of a survey to quantify the awareness of Ghanaian patients on ADRs and ADR-reporting, and in-depth interviews to explore how patients recognize an ADR and the steps they take thereafter. Participants were selected from 28 health care facilities (HCF) in rural and urban areas in 4 out of the 10 administrative regions of Ghana. Chi-square tests were used to examine associations between demographic variables and i) awareness of ADRs and ADR-reporting, ii) ADR experience and iii) awareness of the Ghana Food and Drug Authority (Ghana-FDA) and its patient reporting system (PRS). Only participants that indicated they experienced an ADR were included for the in-depth interviews. Data was investigated for participants' awareness of ADRs, ADR reporting and steps taken when they experience ADRs. Results Of the total 572 participants enrolled in the study, 14% indicated they were unaware of ADRs and were excluded. Of the remaining 491 participants, 38% had experienced an ADR, of which 67% reported the ADR, 68% of them reported it to a doctor. Only 3% of the 491 participants were aware of the Ghana-FDA's PRS. The interview phase consisted of 33 patients who had experienced an ADR. Three key findings from the interview phase were; most participants recognized an ADR themselves, the symptoms of the ADR were the most mentioned reason for reporting and participants experienced a wide variety of obstacles in ADR-reporting. Conclusions Most Ghanaian patients appear unaware of or unable/unwilling to use formal national channels for ADR reporting like the Ghana-FDA PRS. Motivation for ADR reporting appeared mainly personal and not communal. These findings warrant further attention in order to increase patient reporting of ADRs.